2018
DOI: 10.1002/asia.201701807
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Ordered Three‐Dimensional TiO2 Channels for Enhanced Visible‐Light Photocatalytic Performance in CO2 Conversion Induced by Au Nanoparticles

Abstract: As a typical photocatalyst for CO reduction, practical applications of TiO still suffer from low photocatalytic efficiency and limited visible-light absorption. Herein, a novel Au-nanoparticle (NP)-decorated ordered mesoporous TiO (OMT) composite (OMT-Au) was successfully fabricated, in which Au NPs were uniformly dispersed on the OMT. Due to the surface plasmon resonance (SPR) effect derived from the excited Au NPs, the TiO shows high photocatalytic performance for CO reduction under visible light. The ordere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 54 publications
(190 reference statements)
0
6
0
Order By: Relevance
“…This work highlights that the rational design and control of novel nano/micro structures could effectively increase their surface area and porosity, resulting in an enhanced CO 2 photoreduction and adsorption. Besides Bi 2 WO 6 hollow microspheres, various kinds of other hierarchical photocatalysts have been fabricated by different strategies and widely applied in the photocatalytic CO 2 reduction, such as ordered macro/mesoporous TiO 2 sponges or microspheres, TiO 2 photonic crystals (slow photon effect), , TiO 2 nanorod array@carbon cloth, Ti 0.9 O 2 –graphene hollow spheres, TiO 2 –graphene architectures, , CdIn 2 S 4 microspheres, Mn 0.8 Cd 0.2 S microspheres, Zn 1.7 GeN 1.8 O hyperbranched nanostructures, porous TaON microspheres, BiOBr microspheres, cadmium–aluminum LDH microspheres, NaTaO 3 hierarchical porous structure, Bi-rich Bi 4 O 5 Br x I 2– x microspheres, tree trunk derived tantalates MTaO 3 (M = Li, Na, K), 3D ordered mesoporous Fe-doped CeO 2 and TiO 2 /CeO 2 , , CdS@CeO 2 core/shell microspheres, CeO 2 /Bi 2 MoO 6 heterostructures, Bi 2 S 3 /CeO 2 superstructure, foam-like Cu 2 O structure, flower-like CdS/CdV 2 O 6 , flower-like Zn x Ca 1– x In 2 S 4 , TiO 2 nanofibers, irregular CoTe nanoflakes, flower-like Bi 2 WO 6 , ,, Bi 2 S 3 urchin-like microspheres, CuO–TiO 2 hollow microspheres, ZnV 2 O 6 nanosheets, double-shelled ZnGa 2 O 4 hollow spheres, ZnO/NiO porous hollow spheres, LaPO 4 hierarchical hollow spheres, β-SiC hollow spheres, zinc germanium oxynitride hyperbranched nanostructures, graphene–g-C 3 N 4 sandwich-like nanostructures, porous O-doped graphitic carbon nitride (g-C 3 N 4 ) nanotubes, sandwich-like ZnIn 2 S 4 –In 2 O 3 hierarchical tubular heterostructures, In 2 S 3 –CdIn 2 S 4 heterostructured nanotubes, 3D ZnIn 2 S 4 nanosheets/TiO 2 nanobelts, N-doped carbon@NiCO 2 O 4 double-shelled nanoboxes, flower-like Bi 2 MoO 6 microspheres, alkaline tantalates MTaO 3 (M = Li, Na, K), ATiO 3 (A=Sr, Ca, Pb), SrTiO 3 leaf’s 3D architecture, ZnGa 2 O 4...…”
Section: Fundamentals Of Heterogeneous Co2 Photoreductionmentioning
confidence: 99%
“…This work highlights that the rational design and control of novel nano/micro structures could effectively increase their surface area and porosity, resulting in an enhanced CO 2 photoreduction and adsorption. Besides Bi 2 WO 6 hollow microspheres, various kinds of other hierarchical photocatalysts have been fabricated by different strategies and widely applied in the photocatalytic CO 2 reduction, such as ordered macro/mesoporous TiO 2 sponges or microspheres, TiO 2 photonic crystals (slow photon effect), , TiO 2 nanorod array@carbon cloth, Ti 0.9 O 2 –graphene hollow spheres, TiO 2 –graphene architectures, , CdIn 2 S 4 microspheres, Mn 0.8 Cd 0.2 S microspheres, Zn 1.7 GeN 1.8 O hyperbranched nanostructures, porous TaON microspheres, BiOBr microspheres, cadmium–aluminum LDH microspheres, NaTaO 3 hierarchical porous structure, Bi-rich Bi 4 O 5 Br x I 2– x microspheres, tree trunk derived tantalates MTaO 3 (M = Li, Na, K), 3D ordered mesoporous Fe-doped CeO 2 and TiO 2 /CeO 2 , , CdS@CeO 2 core/shell microspheres, CeO 2 /Bi 2 MoO 6 heterostructures, Bi 2 S 3 /CeO 2 superstructure, foam-like Cu 2 O structure, flower-like CdS/CdV 2 O 6 , flower-like Zn x Ca 1– x In 2 S 4 , TiO 2 nanofibers, irregular CoTe nanoflakes, flower-like Bi 2 WO 6 , ,, Bi 2 S 3 urchin-like microspheres, CuO–TiO 2 hollow microspheres, ZnV 2 O 6 nanosheets, double-shelled ZnGa 2 O 4 hollow spheres, ZnO/NiO porous hollow spheres, LaPO 4 hierarchical hollow spheres, β-SiC hollow spheres, zinc germanium oxynitride hyperbranched nanostructures, graphene–g-C 3 N 4 sandwich-like nanostructures, porous O-doped graphitic carbon nitride (g-C 3 N 4 ) nanotubes, sandwich-like ZnIn 2 S 4 –In 2 O 3 hierarchical tubular heterostructures, In 2 S 3 –CdIn 2 S 4 heterostructured nanotubes, 3D ZnIn 2 S 4 nanosheets/TiO 2 nanobelts, N-doped carbon@NiCO 2 O 4 double-shelled nanoboxes, flower-like Bi 2 MoO 6 microspheres, alkaline tantalates MTaO 3 (M = Li, Na, K), ATiO 3 (A=Sr, Ca, Pb), SrTiO 3 leaf’s 3D architecture, ZnGa 2 O 4...…”
Section: Fundamentals Of Heterogeneous Co2 Photoreductionmentioning
confidence: 99%
“…Considering the long-term stability, the hTS 200-12 photocatalyst with optimized hydrothermal pH value and cavity size was examined under irradiation for 24 h. As can be seen in Figure S4, there was no decay observed on CO and CH 4 production rates within 24 h, which shows computable stability among the TiO 2 -based photocatalysts [28][29][30].…”
Section: Effect Of the Hts200-12/graphene Ratio On Its Photocatalytic...mentioning
confidence: 95%
“…Recently, it has been reported that metal particles (such as Au, Ag, Cu, etc. ) with localized surface plasmon resonance (SPR) effects show great potential in the reduction of CO 2 , 21,22 which greatly improves the light absorption performance and the separation efficiency of photogenerated charges of semiconductors. 12,22–25 In particular, in metal oxide catalytic systems, semiconductors with wide bandgaps can be regarded as the hot hole collectors, leaving a large number of hot electrons on the surface of the metal for the reduction of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…with localized surface plasmon resonance (SPR) effects show great potential in the reduction of CO 2 , 21,22 which greatly improves the light absorption performance and the separation efficiency of photogenerated charges of semiconductors. 12,22–25 In particular, in metal oxide catalytic systems, semiconductors with wide bandgaps can be regarded as the hot hole collectors, leaving a large number of hot electrons on the surface of the metal for the reduction of CO 2 . Besides, the Schottky junction formed at the interface between the metal and semiconductor could capture photogenerated electrons, greatly promoting the separation of photoinduced carriers.…”
Section: Introductionmentioning
confidence: 99%